Chromatographic isolation and spectroscopic identification of phytoconstituents of jujuba seeds (Zizyphus jujuba Mill.) - Md Manowwar Alam; Abuzer Ali; Mohammad Ali; Showkat R Mir (Wolters Kluwer Medknow Publications, 2017)
Background: The seeds of Zizyphus jujuba Mill. (Rhamnaceae) are astringent, aphrodisiac, tonic; used to cure cough, asthma, vomiting, burning sensation, biliousness, leucorrhoea, and eye infections in traditional systems of medicine. Materials and Methods: The methanol extract of seeds of Z. jujuba was partitioned into petroleum ether and water soluble fractions. Isolation of compounds was performed by silica gel column chromatography. The structures of isolated compounds were established on the basis of spectral studies and chemical reactions. Results: Chromatographic separation of methanolic extract of seeds yielded three new phyto-constituents characterized as 3, 5, 7-trimethoxy-8, 3', 4', 5'-tetrahydroxy flavone-6-oxy hexahydrobisabolene ether (4), 1, 9-dihydroxy tetrahydrogeranyl-8-oxy-O-β-D-glucuronopyranoside (5) and terahydrogeranyl-8-oxy-O-β-D-glucuronopyranosyl (2a→1b)-O-β-D-glucofuranosyl (2b→1c)-O-β-D-glucofuranosyl (2c→1d)-O-β-D-glucopyranosyl (2d→1e)-O-β-D-glucopyranosyl (2c→f)-O-β-D-glucopyranosyl-2f-benzoate (6) along with five known compounds, palmitoyl palmitoleoyl arachidoyl glyceride (1), tetratriacontenoic acid (2), palmitoyl oleoyl linolenoyl glyceride (3), hexanyl tetraglucoside (7) and pentasaccharide (8). Conclusion: This is the first report of saturated monoterpene and sesquiterpene derivatives from jujuba seeds.